Reallocating Time from Sedentary Behavior to Light and Moderate-to-Vigorous Physical Activity: What Has a Stronger Association with Adiposity in Older Adult Women? - Pelclová, Jana; Štefelová, Nikola; Hodonská, Jana; Dygrýn, Jan; Gába, Aleš; Zając-Gawlak, Izabela (International journal of environmental research and public health, 2018)
This study is the first to use compositional data analysis to investigate movement behaviors of elderly women and their relationships with fat mass percentage (FM%). The focus of the study is on the associations of time reallocations from sedentary behavior (SB) to light physical activity (LIPA) or moderate-to-vigorous physical activity (MVPA) with adiposity. Over 400 older adult women were recruited as part of the cross-sectionally conducted measurements of older adults aged 60+ in Central European countries. An accelerometer was used to assess daily movement behaviors. Body mass index (BMI) and fat mass percentage (FM%) were assessed as adiposity indicators using InBody 720 MFBIA. Using LS-regression, we found positive relationships of BMI and FM% with SB (relative to remaining movement behaviors) (p < 0.001 for both), while their relationship with MVPA (relative to remaining movement behaviors) were negative (p < 0.001 for both). The estimated BMI and FM% associated with a 30-min SB-to-MVPA reallocation were reduced by 1.5 kg/m² and 2.2 percentage points, respectively, whereas they were not reduced significantly with the reallocation of 30 min from SB to LIPA. The findings highlight that SB and MVPA, but not LIPA, are significantly associated with adiposity in elderly women. The reallocation of time from SB to MVPA could be advocated in weight loss interventions in older women.
Keywords: Sedentary Behavior; Cross-Sectional Studies; adipozita; adiposity; Europe; Aged; senioři; BMI; Exercise; Central Europe; compositional data analysis; Evropa; Time Factors; lidé; sedavý životní styl; ženské pohlaví; fat mass; Humans; Body Mass Index; Adiposity; časové faktory; průřezové studie; movement behaviors; index tělesné hmotnosti; Female; cvičení; lidé středního věku; Middle Aged